PENGARUH DOSIS PUPUK BOKASHI KOTORAN PUYUH DAN POC URINE KELINCI TERHADAP HASIL TANAMAN KUBIS BUNGA (Brassica oleracea var. botrytis L.) - Kopral Borahima, Lutfi Ahsanatin; Sunaryo, Yacobus; Darnawi; Sumarwoto (Universitas Sarjanawiyata Tamansiswa, 2023)
The aim of this study was to determine the effect of giving quail manure bokashi fertilizer doses and rabbit urine liquid fertilizer on the yield of cauliflower (Brassica oleracea var. botrytis L.). This research was conducted from December 2022 to March 2023 in the yard which is located in Rejowinangun Village, Kotagede District, Special Region of Yogyakarta, with an altitude of 98 m above sea level, has a temperature of 27OC to 33OC. This study used a 3 x 2 factorial experiment, which was arranged in a Randomized Complete Block Design(RBCD) with 4 replications. The first factor was the dose of quail manure bokashi fertilizer which consisted of three levels: the dose of quail manure bokashi fertilizer was 5 tons/ha (B1), the dose of quail manure bokashi fertilizer was 10 tons/ha (B2), and the dose of quail manure bokashi fertilizer was 15 tons/ha. ha (B3). The second factor was rabbit urine liquid fertilizer (K0) which consisted of two levels: without the aplication of rabbit urine liquid fertilizer of 600 ml/ 1 liter of water per plot (K1). Data were analyzed using variance to determine the effect of treatment on variables then followed by DMRT (Duncan's Multiple Range Test). Parameters observed were leaf number, leaf length, leaf width, leaf chlorophyll content, stem diameter, flower diameter, flower length, and flower fresh weight. The results showed that three was no interaction between the dose of rabbit urine liquid fertilizer on the yield (fresh weight of flower). And adminstration between doses of quail manure bokashi fertilizer and aplication of rabbit urine liquid fertilizer did not significantly affect on the yield (fresh weight of flowers). Keywords: Quail Manure Bokashi Fertilizer, Rabbit Urine POC, Cauliflower